On the Symplectic Structures in Frame Bundles and the Finite Dimension of Basic Symplectic Cohomologies - Czarnecki, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We present a construction (and classification) of certain invariant 2-forms on the real symplectic group. They are used to define a symplectic form on the quotient by a maximal torus and to "lift" a symplectic structure from a symplectic manifold to the bundle of frames. This is a by-product of a failed attempt to prove certain finiteness theorems for basic symplectic cohomologies. In the last part of the paper, we include a valid proof.